"We Have a Long Way to Go:" A Case Study Examination of Older Women Veterans' Experiences in VA Primary Care. (June 2020) - Silvestrini, Molly; Nicosia, Francesca; Spar, Malena J.; Gibson, Carolyn J.; Brown, Rebecca T.
Women Veterans are a growing population with complex care needs. While previous research has examined the experiences of women Veterans, little attention has been paid to the specific experiences of older women Veterans. These case studies present the experiences of 2 older women Veterans who have been enrolled in Veterans Affairs (VA) health care for several decades. Results suggest that these older women Veterans have faced gender-specific challenges and barriers throughout their time accessing VA care. The experiences of these participants suggest that they have gender-sensitive needs that are not always addressed by VA primary care and that women's groups are important mechanisms by which they have gained psychological support in a gender-sensitive environment. These cases suggest that access to gender-sensitive services and women-centered spaces are important for these 2 older women Veterans and should be explored in future research.